Vernakularna arhitektura ali kompleksnost preprostosti - Juvanec, Borut (AR. Arhitektura, raziskave, 2004)
Vernacular architecture is architecture intended for humans and their day-to-day activities. It is not high architecture for kings, gods or the dead; it is not a monument. Research of vernacular architecture is rare: even earlier authors, when writing about architecture, saw only high architecture, above all monuments. This is the paradox: supreme knowledge is in understanding small things. Scientific work lies in discovering, often the most difficult, but also most important element, as well as analytical work in various fields. Theory controls with knowledge. The square root of two is the diagonal of a square; in practise we can see it as the largest square of a round tree trunk. An example of this principle is the Slovenian hayrack. The square root of three halves defines the structure of corbelling; theoretically it represents the height of an equilateral triangle and can be proved after Pythagoras. In practise it is a game played by shepherds: three sticks of equal length define the height of a stone shelter and these have been known since three millennia BC all over the world. Today there is no vernacular architecture: it is a memory of our forefather's culture, which demands recognition, respect and above all, nourishing as heritage. Vernacular architecture is implementation of theory in practise in the simplest possible way. The most complicated solutions have their roots in simplification. The essence is harmony, active balancing of procedures, work, structure and composition itself both in space as well as time.
Keywords: architecture; arhitektura; vernakularna arhitektura; teorija; theory; culture; kultura; kulturna dediščina; cultural heritage